Description of Stunting Incident Factors in Children Based on Trancultural Nursing in the Work Area of Health Center - Nour Sriyanah; Ilham Syam; Suradi Efendi; Hasriani Hasriani; Satriana Dardi (Jurnal Keperawatan, 2022)
Stunting is a condition in which failure to grow in children under five years old is caused by chronic malnutrition so that the child is too short for his age. The purpose of this study is the known description of stunting incident factors in children aged 24-59 months based on trancultural nurisng in the working area of Kahu Health Center of Kahu District of Bone Regency. This type of research is with a descriptive approach. The results of this study were obtained using questionnaires, with the technique of taking a total sampling sample so that a sample of 49 people was obtained. The results of the study found description of low educational factors (75.5%), high family support factors (57.1%), and low economic factors (98.0%) about the incidence of stunting in children. The age 24-59 months based on trancultural nurisng. The conclusion is the known picture of stunting incident factors in children aged 24-59 months based on trancultural nurisng in the working area of Kahu District Kahu District of Bone.